ANALISIS PERBANDINGAN TINGKAT KESEHATAN ANTARA BANK UMUM MILIK NEGARA DAN BANK UMUM MILIK SWASTA - admin, SURIANA B11112018 (Jurnal Manajemen Update, 2016)
Financial performance is used to assess the financial condition and achievements of the company. The performance measurement is used as evaluation for company in order to improve and or increase company performance, and to find an alternative if company experience financial problems. To measure the performance of a company, some benchmarks that are used include ratios and indexes. Bank Indonesia, in assessing the health or performance of a bank, use CAMEL methodology. The purpose of this study was to analyze whether there are differences between the financial performance of State-Owned Commercial Bank and Commercial Bank Private Owned 2010-2014. The population in this study is the banks listed on the Indonesia Stock Exchange (BEI) in the period 2010-2014. Data were collected using purposive sampling method. The sample in this study are four state-owned banks and private banks 5. Financial performance indicators measured by CAMEL consisting of the CAR, NPL, NPM, ROA, ROA and LDR. Data analysis was performed using SPSS 16, with analysis testing Independent Sample T-Test. The results showed that when measured using CAR, NPL, and LDR, there are no differences between state-owned and private banks. However, if it is viewed from the ratio of NPM, ROA and ROA, there are difference between the state of public and private banks. Keywords: Financial Performance, state-owned banks, private banks, CAMEL.